"La mort du conseil spécial est la meilleure action que ce corps ait faite durant sa vie […]": The French-Canadian Press and the Special Council of Lower Canada, 1838–1841. (December 2016) - Dagenais, Maxime
Abstract : On 10 February 1838, months following the 1837 Lower Canada Rebellion, the population of Lower Canada lost all political rights and a political voice. While the British Government attempted to figure out what to do with its disobedient colony, it suspended the 1791 Constitution, dissolved the Legislative Assembly, and put in place an "authoritarian" Special Council to govern the colony. How did French Canadians react to this tutelage? While historians have examined the council's ordinances, few have considered the response of the local French-Canadian population. This article examines the reaction of French Canadian newspaper editors to the Special Council. Their reaction demonstrates that, despite a more difficult and repressive climate and concerns over censorship, editors consistently opposed the Special Council when it acted against the interests of the French Canadian population.